Predictive Value of a Noninvasive Serological Hepatic Fibrosis Scoring System in Cirrhosis Combined with Oesophageal Varices - Feiyue Zhang; Tong Liu; Pan Gao; Sujuan Fei (Canadian Journal of Gastroenterology and Hepatology)
Objective. In recent years, the noninvasive serological scoring system has become a research hotspot in predicting hepatic fibrosis and has achieved good results. However, it has rarely been applied to the prediction of oesophageal varices. The aim of the study was to evaluate the predictive value of the four following scoring systems in cirrhosis combined with oesophageal varices: aspartate and platelet ratio index (APRI), aspartate aminotransferase-alanine aminotransferase ratio (AAR), FIB-4, and S index. Methods. A total of 153 patients with cirrhosis were categorized into groups with or without oesophageal varices. In addition, cirrhosis patients with oesophageal varices were further divided into mild, moderate, and severe grades. The rank sum test was used to compare the significant differences of APRI, AAR, FIB-4, and S index between the two groups of cirrhosis patients with or without oesophageal varices. A ROC curve was generated to compare the area under the curve of the three groups and to obtain the corresponding optimal prediction value. Moreover, multivariate logistic regression analysis was employed to assess the predictive factors for cirrhosis combined with oesophageal varices. Results. 44 patients had no oesophageal varices and 108 patients had oesophageal varices. Of the 108 patients with oesophageal varices, 43 were mild, 32 were moderate, and 33 were severe. The rank sum test indicated that the APRI, FIB-4, and S index were statistically significant between two groups (P < 0.05), while no significant difference was detected in terms of AAR between the two groups (P > 0.05). In addition, all four scoring systems were statistically significant between nonoesophageal varices group and severe oesophageal varices group (P < 0.05). In the ROC curve of oesophageal varices, the AUC values of APRI, FIB-4, and S index for predicting oesophageal varices were 0.681, 0642, and 0.673, respectively. However, in the ROC curve of severe oesophageal varices, the AUC values of APRI, AAR, FIB-4, and S index were 0.729, 0.648, 0.673, and 0.695, respectively. Multivariate logistic regression analysis indicated that APRI and FIB-4 were predictors of disease progression (P < 0.05). Conclusion. AAR harboured a poor predictive value for oesophageal varices, APRI can be used as a reference index for the prediction of severe oesophageal varices, and the S index harboured potential value in predicting the degree of progression of cirrhosis.